Endoglin germline mutation in a patient with hereditary haemorrhagic telangiectasia and dexfenfluramine associated pulmonary arterial hypertension. Issue 5 (28th April 2004) - Chaouat, A; Coulet, F; Favre, C; Simonneau, G; Weitzenblum, E; Soubrier, F; Humbert, M
Abstract : Dexfenfluramine associated pulmonary arterial hypertension occurring in a patient with hereditary haemorrhagic telangiectasia related to a mutation within the endoglin gene is described. This report highlights the critical role of the TGF-β signalling pathway in this condition.